Predictive Impact on Medium-Term Mortality of Hematological Parameters in Acute Coronary Syndromes: Added Value on Top of GRACE Risk Score - Timóteo, AT (2017)
BACKGROUND: Red Cell Distribution Width (RDW) prognostic value in patients with Acute Coronary Syndrome (ACS) has been well validated whereas that of Platelet Distribution Width (PDW) is less well known. OBJECTIVES: Investigate the incremental prognostic value, on top of GRACE risk score, of a new variable resulting from the combination of RDW and PDW. METHODS: Consecutive patients with ACS. Complete blood count, with RDW and PDW, was obtained. Primary endpoint was one-year all-cause mortality and Cox regression models were used to measure the influence of RDW and PDW on patients' survival time. A new combination categorical variable (RDW/PDW) was created with both discretized RDW and PDW and logistic regression models were used. Predictive value and discriminative ability of the model with GRACE risk score alone and of the model with inclusion of RDW/PDW was assessed. RESULTS: We included 787 patients. Hospital and one-year mortality rates were 5.1% and 7.8%, respectively. Both continuous RDW and PDW were independent predictors of death. The best cut-off for RDW was 13.9%, and 14.5% for PDW. Inclusion of RDW/PDW in a model with GRACE risk score improved the AUC from 0.81 (95% CI 0.75-0.86) to 0.84 (95% CI 0.79-0.90) (p=0.024) with an improvement in total NRI (56%) and IDI (0.048). CONCLUSIONS: Simple markers such as RDW and PDW can be useful in risk stratification of death after ACS. Combining both markers with GRACE risk score improved the predictive value for all-cause mortality and reduced the estimated risk of those who did not die.